Tropical Pines in India-an overview - Pandet, G. C. (Indian Forester, 1982)
Pines are the ’in species’ today. The developing countries in the tropics have been raising large scale plantations of pines and this activity is on the increase. Pinus caribaea and Pinus patula have been planted so extensively that the area under plantations exceeds substantially the area occupied by these species in their natural habitat. The paper discusses in various considerations like ’Donor Regions’ climatic condition-specially the temperature and rainfall effects which should be taken into account in selecting the suitable species and lists some of these factors for the important species illustrating the point with examples from local and foreign habitats where pines have been grown. There is already an estimated 3200 ha of land brought under tropical pines in India. The potential is, however, very large. The potential areas and the species are also listed. Provenance research is extremely important for species having a large distribution. The various provenances within Pinus caribaea and Pinus oocarpa are listed and their important features given. The performance of important species like Pinus caribaea, Pinus oocarpa. Pima patula, Pinus kesiya, Pinus greggii and Pinus elliottii in various trial centres is discussed. The importance of inland provenances of Pinus caribaea in India is brought out by analysis of results of provenance trials. Emphasis has been laid on the introduction of better forms of Pinus kesiya from Vietnam and Philippines. Problems of seed procurement and of seed setting are discussed and the future line of work is indicated.